Study on the Consensus Salary System for Modern Enterprises - Li, Zhihong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
For firms, the salary issue is extremely important for their business operations and development. In order to investigate this issue and to expand the role of the salary system in business management, the book presents the Consensus Salary Model for modern enterprises and further explores its theoretical foundations, decisive mechanisms and features, and provides a basic framework for designing salary systems for modern enterprises. Finally, the book incorporates empirical research to test the model.
Introduction -- Summary of the Salary Theory and its Relative Theories -- Main Ideas, Research Approaches and Innovation of the Book -- Analysis of the Existent Salary System of Enterprises -- Institutional Background and Theoretic Foundation of the Consensus Salary System -- Features of the Consensus Salary Model -- Decisive Mechanism of the Consensual Salary Model -- Framework of the Consensual Salary Model -- Design of the Consensus Salary System for the Enterprise M -- Conclusion.
Keywords: Economics; Labor economics; Economics/Management Science; Human Resource Management; Labor Economics